Panu Pihkala, Early Ecotheology and Joseph Sittler - Anker, Peder (Journal for the Study of Religion, Nature and Culture, 2018)
Panu Pihkala, Early Ecotheology and Joseph Sittler (Zürich: Lit Verlag, 2017), 306pp., €44.90 (pbk), ISBN: 978-3-643-90837-7.